2020
DOI: 10.1080/02713683.2020.1762228
|View full text |Cite
|
Sign up to set email alerts
|

TBL1XR1 Mutations in Primary Marginal Zone Lymphomas of Ocular Adnexa are Associated with Unique Morphometric Phenotypes

Abstract: Supplemental Figure 2: PCR of C. psittaci. PCR results showing absence of C. psittaci DNA in all analyzed samples. PCR amplification was performed using primers against pmp gene of C. psittaci (lanes 16 -29) and GAPDH as positive control (lane 1 -14). All samples showed amplification of GAPDH suggesting presence of human genomic DNA but showed no band in all corresponding samples using primers against pmp gene. Lane 30 was the positive control for pmp primers where C. psittaci DNA was added to human genomic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Venturutti et al (25) found through studies in mice that TBL1XR1 alterations lead to a striking extranodal immunoblastic lymphoma phenotype that mimics the human disease. Jangam et al (26) performed targeted deep sequencing of 8 ocular adnexal mucosa-associated lymphoid tissue lymphoma (OAML) cases, and identified TBL1XR1 as recurrently mutated in OAML (4/8), where cases of OAML with mutations in TBL1XR1 showed equivalent or increased vascular density compared with cases without mutations in TBL1XR1. Wang et al (27) found that patients with primary testicular lymphoma with the TBL1XR1 mutation had an inferior OS than patients with TBL1XR1 wild type, irrespective of treatment therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venturutti et al (25) found through studies in mice that TBL1XR1 alterations lead to a striking extranodal immunoblastic lymphoma phenotype that mimics the human disease. Jangam et al (26) performed targeted deep sequencing of 8 ocular adnexal mucosa-associated lymphoid tissue lymphoma (OAML) cases, and identified TBL1XR1 as recurrently mutated in OAML (4/8), where cases of OAML with mutations in TBL1XR1 showed equivalent or increased vascular density compared with cases without mutations in TBL1XR1. Wang et al (27) found that patients with primary testicular lymphoma with the TBL1XR1 mutation had an inferior OS than patients with TBL1XR1 wild type, irrespective of treatment therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Jangam et al. ( 26 ) performed targeted deep sequencing of 8 ocular adnexal mucosa-associated lymphoid tissue lymphoma (OAML) cases, and identified TBL1XR1 as recurrently mutated in OAML (4/8), where cases of OAML with mutations in TBL1XR1 showed equivalent or increased vascular density compared with cases without mutations in TBL1XR1 . Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The H&E images were patched at an optical zoom of ×40, uniform width of 68 pixels and height of 57 pixels. MATLAB program (version 2019b; https://www.mathworks.com/ ) was used for image analysis wherein the cells of interest were segmented based on their pixel intensities ( 33 ). The unsharp filter in the Image Processing Toolbox was used to improve the edge contours and contrast among the different cells of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The H&E images were patched at an optical zoom of x40, uniform width of 68 pixels and height of 57 pixels. MATLAB program (version 2019b; https://www.mathworks.com/) was used for image analysis wherein the cells of interest were segmented based on their pixel intensities (33). The unsharp filter in the Image Processing Toolbox was used to improve the edge contours and contrast among the different cells of interest.…”
Section: Methodsmentioning
confidence: 99%